MATERNAL NEUROTIC CONDITIONS AND THEIR INFLUENCE ON THE COURSE OF AGE CRISES IN CHILDREN (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the clinical psychological characteristics of maternal neurotic conditions and their influence on the course of age crises in children. The research highlights how maternal anxiety, depressive tendencies, and hypochondriacal traits affect the intensity and manifestations of developmental crises in children. Empirical findings indicate significant correlations between maternal neuroticism and the severity of crisis-related emotional and behavioral symptoms in children. These results emphasize the importance of clinical psychological support for mothers in order to prevent maladaptive development in children.